Efeitos da expectativa de ensinar e do feedback autocontrolado na aquisição de habilidades motoras - Marco Túlio Silva Batista (2018)
The objective of this study was to verify the effects of learning as well as the self-control of knowledge of results (KR) in motor learning. In order to test that, forty undergraduate students, volunteers of both sexes, were equally divided into four groups: Self-Controlled Group (GA) and Group Expectation to Teach and Self-Control (GEA), which can choose receive KR or not after each trial, the group Yoked Group (GP) and Group Expectation to Teach (GE), which received feedback in paired form to GA. The GEA and GE groups were further instructed that they would have to teach the to-be-learned task to a novice in the next day. The used task was the throwing of a saloon dart with 45 executions in the acquisition phase. After the acquisition phase, participants answered the Intrinsic Motivation Inventory (IMI) and the strategy questionnaire. On the second day, the participants performed ten executions in the retention test and ten in the transfer test. Performance was evaluated through absolute, constant and variable errors. The normality of the data was verified by the Shapiro Wilk normality test. A two-way ANOVA with repeated measures in the second factor (4 groups x 9 blocks) was conducted for the acquisition phase and two two-way ANOVAs for the retention and transfer tests (4 groups x 2 blocks). When necessary, Tukey's post-hoc test was used to locate the differences. The results indicated that GA, GE and GEA were more accurate than GP. The results showed that the GA was better than the other groups in the retention test for constant error. GA and GEA were more consistent than GP in the retention test, but only the GA was more consistent than the GP in the transfer test. The expectation of teaching and the condition of expectation of teaching and self-control favored the increase of motivational aspects scores. The learners adopted different strategies to request KR throughout the acquisition phase. The expectation of teaching has shown benefits to motor learning. However, their effects seem to be less efficient than those of KR self-control. No additional effects were observed from the condition that used both procedures simultaneously.